2022
DOI: 10.1002/1873-3468.14514
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan‐96 in cytochrome P450 BM3 plays a key role in enzyme survival

Abstract: Flavocytochrome P450 from Bacillus megaterium (P450BM3) is a natural fusion protein containing reductase and heme domains. In the presence of NADPH and dioxygen the enzyme catalyses the hydroxylation of long‐chain fatty acids. Analysis of the P450BM3 structure reveals chains of closely spaced tryptophan and tyrosine residues that might serve as pathways for high‐potential oxidizing equivalents to escape from the heme active site when substrate oxidation is not possible. Our investigations of the total number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…1 ) produce superoxide, hydrogen peroxide, or water instead of hydroxylated substrate. We have suggested that electron transport chains in P450 composed of tryptophan (W) and tyrosine (Y) residues participate in the water-producing oxidase shunt to protect the enzyme from damage when substrate hydroxylation is impaired ( 16 21 ).…”
mentioning
confidence: 99%
“…1 ) produce superoxide, hydrogen peroxide, or water instead of hydroxylated substrate. We have suggested that electron transport chains in P450 composed of tryptophan (W) and tyrosine (Y) residues participate in the water-producing oxidase shunt to protect the enzyme from damage when substrate hydroxylation is impaired ( 16 21 ).…”
mentioning
confidence: 99%
“…Thus, certain protective mechanisms must exist to protect against oxidative damage. One possible mechanism, proposed by Gray and Winkler, suggests that successive electron transfer reactions through a chain of redox-active residues (like tryptophan, methionine, and tyrosine) could eventually deliver the radical to the protein’s surface. This action would defuse the ‘redox bomb’ at the catalytic center .…”
Section: Discussionmentioning
confidence: 99%
“…Rosetta simulations identified mutation to Phe as the lowest energy solution. While replacing Trp with Phe could still allow aromatic ring coupling with W178 in theory, previous studies have shown that Phe impedes transference of holes relative to Trp [57]- [59]. Fig.…”
Section: Mapping Of the Tryptophanyl Featurementioning
confidence: 97%